Point-scale IWV and zenith total delay (ZTD) derived for 66 stations of the global navigation satellite system (GNSS) Upper Rhine Graben network (GURN) - Peng Yuan; Hansjörg Kutterer (PANGAEA, 2021)
The ground-based global navigation satellite system (GNSS) technic was employed to retrieve the integrated water vapor (IWV) at 66 stations of the GNSS Upper Rhine Graben network (GURN). The GNSS IWV dataset is synchronous with the associated InSAR dataset, with 219 days available during the period March 2015 – July 2019. GNSS zenith total delay (ZTD) estimates are calculated every one hour and then converted to IWV with additional meteorological parameters from ERA5. The GNSS IWV of all the stations are saved in daily files in the second version of the Solution (Software/Technique) Independent Exchange (SINEX) format for TROpospheric parameters. GNSS station information is given in the file headers. In addition, the associated meteorological parameters from ERA5 are also provided, such as station pressure and weighted mean temperature.
In: Fersch, Benjamin; Kamm, Bettina; Shehaj, Endrit; Wagner, Andreas; Yuan, Peng; Möller, Gregor; Schenk, Andreas; Geiger, Alain; Hinz, Stefan; Kutterer, Hansjörg; Kunstmann, Harald (2021): A comprehensive high resolution data collection for tropospheric water vapor assessment for the Upper Rhine Graben, Germany [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.936447